MIRERC080/2025: ASSESSMENT OF THE IMPACT OF WASTEWATER POLLUTION IN HONI RIVER IN NYERI COUNTY, KENYA - Ezekiel Mengo, Marigi; Dr. Lucas Mogaka; Dr. George N. Mungai (MUST Institutional Research Ethics Review Committee (MIRERC), 2025)
Wastewater pollution is a growing global concern with significant environmental and public health implications, particularly in developing and rapidly urbanizing regions. The Honi River in Mweiga, Nyeri County, Kenya, is increasingly threatened by wastewater pollution from overloaded sanitation systems, informal discharges, poor waste management, and agricultural activities. The study will assess the extent of wastewater pollution in the Honi River. It will involve mapping the spatial distribution of pit latrines, septic tanks, and human activities such as farming or industry along the river, evaluating water quality, and linking the presence of enteric pathogens to waterborne diseases in the community. A descriptive and experimental research design will be used. Pit latrines, septic tanks, and human activities within 200 m of the river will be mapped using Global Positioning System and Geographic Information System tools. Structured questionnaires will measure sanitation practices, infrastructure use, and human activities near the riparian land. Water samples will be collected from upstream, middle, and downstream sites to analyse physicochemical parameters such as temperature, pH, turbidity, electrical conductivity, total dissolved solids, chemical oxygen demand, biological oxygen demand, and nutrients (nitrates and phosphates). Microbial indicators, including E. coli, Shigella, Salmonella, and Giardia, will be analysed using both conventional methods and polymerase chain reaction-based molecular techniques. Heavy metals like lead will be determined using inductively coupled plasma-mass spectrometry. Health data from local health facilities will be used to estimate the prevalence of waterborne diseases, which will then be correlated with pathogen presence and proximity to sanitation facilities through spatial and statistical analyses. The expected outcomes include a comprehensive water quality profile, identification of pollution hotspots, and a clarified relationship between sanitation infrastructure and disease burden. The findings will support policy recommendations for wastewater management and sanitation infrastructure improvements, contributing to public health protection and sustainable water resource management in semi-urban Kenyan settings.